Pharmacovigilance Study of Infigratinib: A Safety Analysis of the FDA Adverse Event Reporting System - Dehua Zhao; Xiaoqing Long; Jiping Zhou; Jisheng Wang (Adis, Springer Healthcare, 2023)
Abstract Background Infigratinib is a fibroblast growth factor receptor (FGFR)-specifc tyrosine kinase inhibitor indicated for the treatment of patients with previously treated, unresectable, locally advanced or metastatic cholangiocarcinoma. However, few studies have been conducted to evaluated the safety of infigratinib in the real world. In this study, we conducted a pharmacovigilance study to evaluate the adverse events (AEs) of infigratinib by using the Food and Drug Administration Adverse Event Reporting System (FAERS) database. Methods OpenVigil 2.1 was employed to extract the FAERS database. Descriptive analysis was used to describe the characteristics of infigratinib-associated AE reports. Disproportionality analysis was performed by calculating the proportional reporting ratio (PRR), reporting odds ratios (ROR), and Bayesian analysis confidence propagation neural network (BCPNN) to detect positive signals. Results Our findings revealed 149 AE reports, among which 36 significant signals were identified. These significant AE signals were mainly observed in gastrointestinal disorders (N = 26, ROR = 26.03, PRR = 8.44, information component [IC] = 3.08) and skin and subcutaneous tissue disorders (N = 21, ROR = 92.13, PRR = 40.41, IC = 5.34). Notably, dehydration and skin exfoliation were unexpected AEs, but had relatively high signal intensities (ROR = 29.75, PRR = 26.64, IC = 4.74; ROR = 50.61, PRR = 45.24, IC = 5.50, respectively) despite not being listed on the drug label. Furthermore, our analysis showed that infigratinib dose differed statistically between severe and non-severe reports (113.82 ± 16.13 mg vs 125 ± 0.00 mg, t = − 4.28; p < 0.001). However, there were no significant differences in sex, age, and types of AEs between the two groups (p  = 0.06, p  = 0.86, and p = 0.93, respectively). Conclusions These findings suggest that gastrointestinal and skin toxicities are the most common adverse reactions for infigratinib. It is important to recognize skin exfoliation and dehydration in clinical practice, as they are unexpected AEs. Additionally, our study indicates that infigratinib dose may correlate with an increased risk of AE severity, highlighting the need for dose adjustment of infigratinib when exposure to the drug is increased due to internal or external factors.